Test of pragmatics - Priya K. Sundaram (Journal of All India Institute of Speech and Hearing, 1970)
The present study was an attempt to develop a pragmatic test in Tamil. It is based on the pragmatic test given by Shulman (1986). It is expected that the test would detect any deficit in the abilities of children to carry on a social exchange, in realistic communicative contexts.